A Matrix Method Based on the Fibonacci Polynomials to the Generalized Pantograph Equations with Functional Arguments. (13th August 2014) - Koç, Ayşe Betül; Çakmak, Musa; Kurnaz, Aydın
Abstract : A pseudospectral method based on the Fibonacci operational matrix is proposed to solve generalized pantograph equations with linear functional arguments. By using this method, approximate solutions of the problems are easily obtained in form of the truncated Fibonacci series. Some illustrative examples are given to verify the efficiency and effectiveness of the proposed method. Then, the numerical results are compared with other methods.